Pemanfaatan E-Commerce Untuk Memperluas Jaringan Pemasaran Produk Olahan Hasil Laut di Desa Randutatah - Ahmad Hudawi AS; Said Agil Asy’ari; Muhammad Naufal (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The implementation of this community service involves this Partner Village located in Randutatah Village, Paiton District, Probolinggo Regency. This group has various businesses, processed seafood. Technology development in the digital era has brought significant changes in various aspects of life, including in business and marketing. E-commerce is one form of technology utilization that is growing rapidly, providing new opportunities for business actors, including farmers and fishermen in Randutatah Paiton Village. However, obstacles such as limited internet access, lack of e-commerce knowledge, low marketing networks, and intense competition on e-commerce platforms are the main challenges.To overcome these obstacles, a training program on e-commerce utilization was conducted. This training program involves business owners and workers, with an implementation method that includes planning, implementing activities, and monitoring and evaluation. The purpose of the implementation of this community service is to apply e-commerce to the sale of various MSME products in Randutatah Village with the intention of introducing and increasing their sales turnover, while the method used is to use participatory methods, counseling, mentoring and training. The results obtained from the implementation of this community service are that with the help of training and e-commerce applications, it can reduce the sales turnover of MSME products in Randutatah Village.